If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -7x + -4 = -28 + 4x + -14 Reorder the terms: 6 + -4 + -7x = -28 + 4x + -14 Combine like terms: 6 + -4 = 2 2 + -7x = -28 + 4x + -14 Reorder the terms: 2 + -7x = -28 + -14 + 4x Combine like terms: -28 + -14 = -42 2 + -7x = -42 + 4x Solving 2 + -7x = -42 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 2 + -7x + -4x = -42 + 4x + -4x Combine like terms: -7x + -4x = -11x 2 + -11x = -42 + 4x + -4x Combine like terms: 4x + -4x = 0 2 + -11x = -42 + 0 2 + -11x = -42 Add '-2' to each side of the equation. 2 + -2 + -11x = -42 + -2 Combine like terms: 2 + -2 = 0 0 + -11x = -42 + -2 -11x = -42 + -2 Combine like terms: -42 + -2 = -44 -11x = -44 Divide each side by '-11'. x = 4 Simplifying x = 4
| 2x-4+9+2=27 | | Y=x-(x-(x*0.2))*0.18 | | 11-5y=26 | | -9d-1=16 | | m-9/3=3 | | 2(3x-1)+2(4x+5)=2x+44 | | 24x+32-2.1x=20.9x+30+x+2 | | 2x-4x+2=27 | | 5z+10=180-z+50 | | 24x-1=47 | | -8x-14=4x+22 | | 4x/12x=1/3 | | 2p+4=-18 | | 12at=4 | | 6x-4x+5=11 | | 0.33w=0.759 | | 1/2x-18=14 | | 36-18=3(x-1) | | 18+2y-3=9y-10-2y | | -2+5(x-4)=13x+2-8x | | -11=v-13 | | 22x-4xy-7x/3xy | | 9x^2-12+8=0 | | -6j+-19j+19j=-12 | | 4f=1/6 | | 7x-15=-2x | | 48+12+x=-12 | | (2x+7)(x-3)(1235x)=0 | | 6+20lnx=2 | | 3x5/32 | | 1x+6=18 | | (m+7)+(2m+1)=20 |